The β2-Subunit of Voltage-Gated Calcium Channels Regulates Cardiomyocyte Hypertrophy - Pickel, Simone; Cruz-Garcia, Yiliam; Bandleon, Sandra; Barkovits, Katalin; Heindl, Cornelia; Völker, Katharina; Abeßer, Marco; Pfeiffer, Kathy; Schaaf, Alice; Marcus, Katrin; Eder-Negrin, Petra; Kuhn, Michaela; et al. (Frontiers in Cardiovascular Medicine, 2021)
L-type voltage-gated calcium channels (LTCCs) regulate crucial physiological processes in the heart. They are composed of the Cavα1 pore-forming subunit and the accessory subunits Cavβ, Cavα2δ and Cavγ. Cavβ is a cytosolic protein that regulates channel trafficking and activity, but it also exerts other LTCC-independent functions. Cardiac hypertrophy, a relevant risk factor for the development of congestive heart failure, depends on the activation of calcium-dependent pro-hypertrophic signaling cascades. Here, by using shRNA-mediated Cavβ silencing, we demonstrate that Cavβ2 downregulation enhances α1-adrenergic receptor agonist-induced cardiomyocyte hypertrophy. We report that a pool of Cavβ2 is targeted to the nucleus in cardiomyocytes and that the expression of this nuclear fraction decreases during in vitro and in vivo induction of cardiac hypertrophy. Moreover, the overexpression of nucleus-targeted Cavβ2 in cardiomyocytes inhibits in vitro-induced hypertrophy. Quantitative proteomic analyses showed that Cavβ2 knockdown leads to changes in the expression of diverse myocyte proteins, including reduction of calpastatin, an endogenous inhibitor of the calcium-dependent protease calpain. Accordingly, Cavβ2-downregulated cardiomyocytes had a two-fold increase in calpain activity as compared to control cells. Furthermore, inhibition of calpain activity in Cavβ2-downregulated cells abolished the enhanced α1-adrenergic receptor agonist-induced hypertrophy observed in these cells. Our findings indicate that in cardiomyocytes, a nuclear pool of Cavβ2 participates in cellular functions that are independent of LTCC activity. They also indicate that a downregulation of nuclear Cavβ2 during cardiac hypertrophy promotes the activation of calpain-dependent hypertrophic pathways.